(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The study was conducted to evaluate the reproductive performance of Brahman crossbred females and compare them with other available cattle genotypes found in Mymensingh district. Reproductive performance data on 35 Brahman crossbreds, 32 Indigenous, 12 Sahiwal crossbreds and 21 Friesian crossbreds were collected from three different villages (Baera, Bhabkhali and Dowhakhola) adjacent to Bangladesh Agricultural University, Mymensingh. Statistical analyses were performed using Statistical Analysis System (SAS) computer program. Reproductive performance of Brahman crossbred was recorded as age at first service: 32.29 ± 1.46 months, age at first calving: 42.00 ± 1.49 months, service per conception: 1.7 ± 0.17, overall conception rate: 0.76 ± 0.05 (76.11%), conception at first service: 0.63 ± 0.08 (62.85%) and gestation length: 282.97 ± 0.78 days. Highly significant (p<0.001) effect of genotype was observed for age at first service and age at first calving; conception rate at first service differs significantly (p<0.05) among genotypes while service per conception, overall conception rate and gestation length were not significantly affected by genotype. Reproductive performance of Brahman crossbred heifer is within the moderate range and better for some traits (i.e. age at first service) than the other genetic groups studied (i.e. Indigenous, Sahiwal × Indigenous, Friesian × Indigenous). J Bangladesh Agril Univ 19(1): 61–66, 2021 https://doi.org/10.5455/JBAU.126665